Gemini 1.5 Flash and Pro Robustness Against Adversarial Perturbations in Diagram Interpretation - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 8 peer-reviewed papers addressing the following research question: What is the comparative robustness of Gemini 1.5 Flash versus Pro against adversarial perturbations in complex diagram interpretation tasks within HumanEval-V. 12 claims were extracted from source literature; 8 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 7.2/10. This report is a machine-generated literature synthe
Machine-generated literature synthesis.